Effectiveness and Waning of Protection With Different SARS-CoV-2 Primary and Booster Vaccines During the Delta Pandemic Wave in 2021 in Hungary (HUN-VE 3 Study) - Vokó, Zoltán; Kiss, Zoltán; Surján, György; Surján, Orsolya; Barcza, Zsófia; Wittmann, István; Molnár, Gergő Attila; Nagy, Dávid; Müller, Veronika; Bogos, Krisztina; Nagy, Péter; Kenessey, István; et al. (Frontiers in Immunology, 2022)
Background In late 2021, the pandemic wave was dominated by the Delta SARS-CoV-2 variant in Hungary. Booster vaccines were offered for the vulnerable population starting from August 2021. Methods The nationwide HUN-VE 3 study examined the effectiveness and durability of primary immunization and single booster vaccinations in the prevention of SARS-CoV-2 infection, Covid-19 related hospitalization and mortality during the Delta wave, compared to an unvaccinated control population without prior SARS-CoV-2 infection. Results The study population included 8,087,988 individuals who were 18–100 years old at the beginning of the pandemic. During the Delta wave, after adjusting for age, sex, calendar day, and chronic diseases, vaccine effectiveness (VE) of primary vaccination against registered SARS-CoV-2 infection was between 11% to 77% and 18% to 79% 14–120 days after primary immunization in the 16–64 and 65–100 years age cohort respectively, while it decreased to close to zero in the younger age group and around 40% or somewhat less in the elderly after 6 months for almost all vaccine types. In the population aged 65–100 years, we found high, 88.1%–92.5% adjusted effectiveness against Covid-19 infection after the Pfizer-BioNTech, and 92.2%–95.6% after the Moderna booster dose, while Sinopharm and Janssen booster doses provided 26.5%–75.3% and 72.9%–100.0% adjusted VE, respectively. Adjusted VE against Covid-19 related hospitalization was high within 14–120 days for Pfizer-BioNTech: 76.6%, Moderna: 83.8%, Sputnik-V: 78.3%, AstraZeneca: 73.8%, while modest for Sinopharm: 45.7% and Janssen: 26.4%. The waning of protection against Covid-19 related hospitalization was modest and booster vaccination with mRNA vaccines or the Janssen vaccine increased adjusted VE up to almost 100%, while the Sinopharm booster dose proved to be less effective. VE against Covid-19 related death after primary immunization was high or moderate: for Pfizer-BioNTech: 81.5%, Moderna: 93.2%, Sputnik-V: 100.0%, AstraZeneca: 84.8%, Sinopharm: 58.6%, Janssen: 53.3%). VE against this outcome also showed a moderate decline over time, while booster vaccine types restored effectiveness up to almost 100%, except for the Sinopharm booster. Conclusions The HUN-VE 3 study demonstrated waning VE with all vaccine types for all examined outcomes during the Delta wave and confirmed the outstanding benefit of booster vaccination with the mRNA or Janssen vaccines, and this is the first study to provide clear and comparable effectiveness results for six different vaccine types after primary immunization against severe during the Delta pandemic wave.